Assessment and analysis of ecological quality, macroinvertebrate communities and diversity in rivers of a multifunctional tropical island. (June 2017) - Forio, Marie Anne Eurie; Lock, Koen; Radam, Eve Daphne; Bande, Marlito; Asio, Victor; Goethals, Peter L.M.
Highlights: We applied ecological indices to assess rivers in a multifunctional tropical island (Philippines). Most rivers have moderate to very good ecological quality and high invertebrate diversity. Sand/gravel quarrying in rivers negatively impacts invertebrate diversity. Distance between sources and marine system are short, thus typical midstream and downstream systems were not encountered. Organic pollution was weakly related to diversity and ecological quality which might be due to low input in most sites. Abstract: This study aims to assess the macroinvertebrate communities, diversity and ecological quality (expressed as BMWP-Viet) of rivers on a tropical island. Environmental factors associated with macroinvertebrate communities, diversity and ecological quality were identified to assist conservation planning and management. Biological (macroinvertebrates), chemical, physical and hydromorphological characteristics of 85 river reaches were assessed in Leyte island, Philippines. Canonical Correspondence Analysis (CCA) and multivariable linear regression (LRM) were performed to relate environmental variables and macroinvertebrates. Several taxa of snails, shrimps, dragonflies, beetles, bugs and caddisflies were found on the island. Although many sites had good to very good ecological quality and high diversity, about 41% had moderate to very bad ecological quality and low diversity. Based on CCA, we can conclude that macroinvertebrate communities were associated with velocity, sediment, conductivity and dissolved oxygen. Particularly, sensitive and tolerant taxa were encountered at high and low flow velocities, respectively. LRM indicated that macroinvertebrate diversity and ecological quality were associated with physical (turbidity), chemical (chlorophyll), hydromorphological characteristics (bank slope & pool/riffle class), habitat degradation (gravel/sand quarrying, erosion) and the presence of logs and twigs. Consequently, this study gives support to the use of invertebrates as indicators of certain environmental conditions and the results of this investigation can serve as a basis to set up dedicated experiments to further prove the causality of these discovered relations. Strikingly, organic pollution, as reflected by biological oxygen demand and chemical oxygen demand, was in general weakly related to invertebrate composition, diversity and ecological quality. This might be linked to the low input in most sites and the relatively short rivers which are closely connected to the marine system. Thus, typical midstream and downstream systems were not encountered and the accumulation of these pollutants along the river is less likely. Although the island is situated in the western Pacific Ocean and encounters intensive natural disturbances (severe typhoons), the taxa (families) are similar to other tropical systems and the effects of the environmental conditions are comparable. Findings of this study are valuable in understanding tropical island systems and provide insights into the effects of environmental conditions on stream invertebrates, which aids in protecting and conserving tropical insular systems.